Service Profit Chain Relation in Commercial Banks: A Study in Kathmandu Valley (The Lumbini Journal of Business and Economics, 2026)
Purpose: The service profit chain (SPC) is an important framework in the banking sector that explains the relationship between internal service quality, employee satisfaction, customer satisfaction, and profitability. This study examines SPC relationships in commercial banks of Kathmandu Valley.Methods: An explanatory research design was adopted using purposive sampling. Data were collected from 384 employees of commercial banks in Kathmandu Valley. The study was grounded in Emotional Contagion Theory and analyzed using descriptive statistics, inferential statistics, and Structural Equation Modeling (SEM).Results: Findings revealed that job design, training and development, rewards and recognition, and tools for serving customers significantly influenced employee satisfaction, while workplace design was insignificant. Employee satisfaction strongly affected customer satisfaction, which in turn significantly enhanced profitability. The model confirmed sequential mediation and supported the applicability of SPC in Nepal’s banking sector.Conclusion: The study concludes that strong internal service quality increases employee satisfaction and productivity, leading to greater customer satisfaction and improved profitability in commercial banks.